Refining Education Quality: A Note on Principal Leadership - Ahmad Muzakki Zen; St. Rodliyah (The Faculty of Education and Teaching Training, 2022)
A successful institution requires a strong and capable leader to lead the institution. One of the Principal's primary duties is to improve the quality of education in the institutions he directs. The quality of education is constantly improving, at least to keep up with the times and to maximize the dynamics of people's lives. Improving the quality of education is therefore characterized by improving student learning outcomes. This study focuses on identifying key leadership types and models for improving the quality of education at SMA 04 Ma'arif Perintis Tempurejo Jember. This study aimed to describe the nature and model of school leadership in improving the quality of education. This research uses a qualitative approach. The type of study used is the field study type—data collection techniques through observations, interviews, and documentary studies. Data analysis techniques used descriptive qualitative analysis with Miles and Huberman's interactive descriptive model of data condensation, data presentation, and inference. Data validity using technical and source triangulation. The results of this study show that the most important type of leadership in improving educational quality is the democratic type of leadership, and the second model of principal leadership to improve educational quality is adequate. It Demonstrates the use of leadership models. Keberhasilan lembaga pendidikan memerlukan seorang pemimpin yang mampu dan tangguh dalam memimpin sebuah lembaga pendidikan. Salah satu tugas utama kepala sekolah adalah meningkatkan mutu pendidikan pada lembaga pendidikan yang dipimpinnya. Mutu pendidikan senantiasa ditingkatkan agar minimal selalu dapat mengikuti perkembangan zaman dan maksimal dapat mewarnai dinamika kehidupan masyarakat. Maka meningkatnya mutu pendidikan ditandai dengan meningkatnya hasil belajar murid. Penelitian ini difokuskan untuk mengungkap bagaimana tipe dan model kepemimpinan kepala sekolah dalam meningkatkan mutu pendidikan di SMA 04 Ma’arif Perintis Tempurejo Jember. Tujuan penelitian ini adalah mendeskripsikan tipe dan model Kepemimpinan Kepala Sekolah Dalam Meningkatkan Mutu Pendidikan. Penelitian ini menggunakan pendekatan kualitatif. Adapun jenis penelitian yang digunakan adalah jenis penelitian field research. Teknik pengumpulan data menggunakan observasi, wawancara dan studi dokumenter. Teknik analisis data menggunakan analisis deskriptif kualitatif dengan model interaktif deskriptif Miles dan Huberman yang terdiri dari kondensasi data, penyajian data dan penarikan kesimpulan. Keabsahan data menggunakan triangulasi teknik dan triangulasi sumber. Hasil penelitian ini menunjukkan bahwa Pertaman tipe kepemimpinan kepala sekolah dalam meningkatkan mutu pendidikan adalah tipe kepemimpinan demokratis dan Kedua Model kepemimpinan kepala sekolah dalam peningkatan mutu pendidikan menggunakan model kepemimpinan yang efektif.